2021
DOI: 10.3390/plants10050981
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide and Comprehensive Analysis of the Multiple Stress-Related CAF1 (CCR4-Associated Factor 1) Family and Its Expression in Poplar

Abstract: Poplar is one of the most widely used tree in afforestation projects. However, it is susceptible to abiotic and biotic stress. CCR4-associated factor 1 (CAF1) is a major member of CCR4-NOT, and it is mainly involved in transcriptional regulation and mRNA degradation in eukaryotes. However, there are no studies on the molecular phylogeny and expression of the CAF1 gene in poplar. In this study, a total of 19 PtCAF1 genes were identified in the Populus trichocarpa genome. Phylogenetic analysis of the PtCAF1 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…The increased expression of these genes during cold acclimation increases freezing tolerance [ 32 , 33 ]. Therefore, based on the results of this study, we can speculate that CpCAF1 is implicated in chilling-response signaling pathways, which may be similar to many CAF1 genes induced by low-temperature treatment, such as AtCAF1 [ 34 ], DsCAF1 [ 35 ], OsCAF1B [ 36 ], and Pt CAF1 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased expression of these genes during cold acclimation increases freezing tolerance [ 32 , 33 ]. Therefore, based on the results of this study, we can speculate that CpCAF1 is implicated in chilling-response signaling pathways, which may be similar to many CAF1 genes induced by low-temperature treatment, such as AtCAF1 [ 34 ], DsCAF1 [ 35 ], OsCAF1B [ 36 ], and Pt CAF1 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the CAF1 gene sequence in Vitis vinifera, Sorghum bicolor, Oryza sativa, and Arabidopsis was confirmed via a full-sequence genomic BLAST search of GenBank for certain plants [ 27 ]. Several CAF1 proteins are vital for plant growth and play essential roles in stress response [ 2 , 28 , 29 , 30 ].The potential function of CAF1 in flower development, however, has been reported previously only once: TaCAF1Ia1, a novel non-typical CAF1 lacking the DEDD domain, is specifically expressed during the early stages of anther development in wheat (Triticum aestivum). It is assumed that a distinct miR2275–CAF1 pathway evolved to regulate reproductive development in wheat [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, unlike animals, plants are sedentary and need to evolve a range of mechanisms to respond to environmental changes, which may involve in the expansion of the CAF1 family. The roles of CAF1 in stress response have been reported in many plants [22] , [23] , [24] , [25] . But studies in mammals have shown that the function of CAF1 is quite important in reproductive development [16] , [17] , [18] , [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the rice homologues were the same as those in yeast and human containing the conserved deadenylase subunits of DEDD domain [21] . More interestingly, most of the studies in Arabidopsis , rice, pepper, citrus and poplar have demonstrated that plant CAF1s are widely involved in both biotic and abiotic stress responses in plants [22] , [23] , [24] , [25] . The role CAF1 may play in plant reproductive development has not been verified.…”
Section: Introductionmentioning
confidence: 99%